Influence of electron scatterings on thermoelectric effect - Li, Jing (2013)
In this work, we employed non-equilibrium Green’s function to investigate the electron transport properties in a nanowire in the presence of scatterings. The scattering mechanism is modelled by the Büttiker probe. The effect of electron scattering is analyzed under three conditions: absence of external field; with a bias voltage; and with a finite temperature difference. It is found that weak and strong scattering strengths affect the electron transport in different ways. In the case of weak scattering strength, electron trapping increases the electron density, thereby boosting the conductance significantly. Although the increment in conductance would reduce the Seebeck coefficient slightly, the power factor still increases. In the case of strong scattering strength, electron diffraction causes the redistribution of electrons; accumulation of electrons at the ends of the wire blocks current flow; hence the conductance is reduced significantly. Although the Seebeck coefficient increases slightly, the power factor still decreases. The power factor is enhanced by 6%−18%, at the optimum scattering strength.